Adsorption of Humic Substances by using Coconut Copra - M.F., Atan; K.A., Mapi; S.N.F., Ghazali; N., Abdul Rahman; S.F., Salleh (Universiti Malaysia Sarawak (UNIMAS), 2014)
Nowadays, consumers are concern about the quality of water that being supplied in order to ensure the water supplied is free from any harmful substances for example like Humic Substances (HS). High concentration of HS in drinking water can cause disease for human such as stomach cancer. Thus, it is important to develop a new technique to improve the quality of drinking water. Therefore, the objective of this research is to investigate the potential of using coconut copra treated with citric acid as activated carbon in adsorbing HS contained in wastewater collected from Asajaya Treatment Plant situated in district of Samarahan, Sarawak. In this research, the optimum condition of adsorption process need to determined. As such, there are two types of parameters which are considered as constant; temperature and pH of activated carbon and variable; solid liquid ratio and residence time. As a result, this research has shown that coconut copra possess the capacity to adsorp 97.5% of HS contained in wastewater.